(untitled) (REME-Revista Mineira de Enfermagem, 2007)
The objective of this study is to get to know the point of view of adult patients about an Intensive Care Unit (ICU). The methodology adopted was qualitative, using a questionnaire answered by 10 patients who were back in the ward and had been in an ICU for at least 48 hours in a University Hospital in Cuiabá. The results showed feelings such as fear, acceptance, support, insecurity and relative frustration. They referred to the work of the nursing team as making a difference in the ICU care and indicate the need to reflect about the humanization of the environment and the work inside this unit.